SINTESIS 4âHIDROKSIâ3âKLOROBENZALDEHID DARI pâHIDROKSIBENZALDEHID DAN GAS Cl2 - Warsi, Warsi (Pharmaciana, 2015)
Curcumin is a compound which potential to be developed. The curcumin analogues havebeen synthesized. The compound 3âchloroâ4âhydroxybenzaldehyde was used as starting material inthe synthesis of curcumin analogues with Cl substituent on the aromatic ring. The compound of3âchloroâ4âhydroxybenzaldehyde were synthesized by chlorination reaction betweenpâhydroxybenzaldehyde and Cl2 gas. The purity of 3âchloroâ4âhydroxybenzaldehyde wasdetermined base on the melting range, thin layer chromatography and LCâMS. The structureidentification of the compound was observed done by spectrometry techniques, including massspectra (ESIâMS), infrared spectra (cm-1, KBr), Nuclear Magnetic resonance proton spectra (Î´, ppm,DMSO-d6, 1HâNMR, 500 MHz) and UVâVis spectra. Chlorination reaction ofpâhydroxybenzaldehyde produced yellow crystal of 3âchloroâ4âhydroxybenzaldehyde, its meltingrange is 128.1 to 130.8ÂºC. The average yield obtained of this reseach is 51.37%.